Rural spatial transformation and governance from the perspective of land development rights: A case study of Fenghe village in Guangzhou. (27th September 2021) - Yang, Ren; Lin, Yuancheng
Abstract: Urban expansion and the demand for sustainable regional economic development make rural land a resource base for spatial regeneration, transformation, and upgrading. From the perspective of land development rights, this paper analyzes the rural spatial transformation mechanism and rural governance logic in Fenghe village, Guangzhou. The results show that: (1) Fenghe village has experienced three stages of rural forming development, "hollowing" and space transformation. The subject of land development rights has shifted from rural collectives and villagers to external capital enterprises. Rural development pathways and land‐use patterns have changed from single to diversified. The space presents trends of community, commercialization and modernization. (2) Changes in the subjects of land development rights have caused the diversification and transformation of rural space. Homesteads, idle agricultural land, industrial formats, and infrastructure have gradually become standardized, market‐oriented, diversified, agglomerated, and systemized. With the diversification, complexity and consumerization of rural living groups, social relations, subject connections and rural spaces tend to be modern development models. (3) The reconstruction of rural space contains the logic of capital games and negotiated governance. Urban capital reaches a benefit balance between rural collective and villagers, obtains the right to rural land development, and forms multi‐subject collaborative governance.